Morphometric analysis of five species of the Gracilaria mammillaris complex (Gracilariaceae, Rhodophyta) in the Mexican Atlantic - Vilchis , Martha Isabel; Dreckmann , Kurt M.; Sentíes , Abel (Instituto de Ecología, A.C., 2022)
Background and Aims: The Gracilaria mammillaris complex is a group of red algae, whose identification is complicated due to the small number of morphological characters that delimit them. This problem is accentuated when they are distributed in the same area. The aim of this work was to determine, through morphometric analysis, the existence of characters that allow and facilitate the delimitation of five species of the Gracilaria mammillaris complex in the Mexican Atlantic. Methods: Twenty-four morphometric characters of five species of the Gracilaria mammillaris complex were subjected to a principal component analysis, to evaluate the existence of a pattern of morphological variation between species. The resulting components were analyzed by means of a NP-MANOVA. The arithmetic means and confidence intervals for the characters with a greater weight in discrimination were calculated and plotted. A UPGMA clustering analysis was performed to support these results. Results: The analyses showed that the only species in the complex that differs was Gracilaria curtissiae, the rest did not show significant differences between them. On average, the length and width of the cortical cells of the medium portion of the thallus were larger in G. curtissiae than in the other species; and the length and width of the medullary cells in the medium portion of the thallus proved to be on average smaller in G. curtissiae than in the other species of the complex. Clustering analysis supports the previous results. Conclusions: An ongoing speciation process could be the answer to the fact that the morphological proprieties of most of the studied species are not yet distinguishable, but the phylogenetic ones are. Future molecular clock and phylogeographic analyses will allow a better understanding of the state of divergence in which these taxa are found.